Effects of Woolwich Massage On Breast Milk Production in Postpartum Mothers in Rokan IV Koto 1 Health Center - Andria, Andria; Wulandari, Sri; Nurkhasanah, Siti; Aroh, Siti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
The flow ASIis influenced by the hormone prolactin while the release ASIis influenced by the hormone oxytocin. Efforts that can be made to stimulate the hormones oxytocin and prolactin in mothers after giving birth are: Woolwich massage . Woolwich massage stimulates the hormones prolactin and oxytocin in postpartum mothers by providing a relaxed sensation to the mother so that it can help breast milk production. The purpose of this study was to determine the effect of Woolwich massage on breast milk production in postpartum mothers in the Rokan IV Koto 1 Health Center work area. This type of research isbeforeexperiment with the design used is pre-test and post-test one group . The population of this study were all postpartum mothers on the second day-30 days totaling 15 people in the working area of the Rokan IV Koto 1 Health Center. The sample in this study was 15 postpartum mothers in the working area of the Rokan IV Koto 1 Health Center obtained by random sampling technique. The sampling technique used in this study was Non Probability Sampling, namely simple random sampling. Data analysis usingnon-parametric test with comparative hypothesis . The results of the analysis obtained that the p- value 0.000 0.05, which means that there is an effect of Woolwich massage on breast milk production in postpartum mothers in the Rokan IV 1 health center work area . It is hoped that after the research is conducted, the health center can implement and introduce methods that can help mothers deal with breastfeeding problems in the first three days after giving birth, especially with the Woolwich massage method.